Chronic kidney disease as a risk factor for recurrence and progression in patients with primary non‐muscle‐invasive bladder cancer. (22nd July 2017) - Kobatake, Kohei; Hayashi, Tetsutaro; Black, Peter C; Goto, Keisuke; Sentani, Kazuhiro; Kaneko, Mayumi; Yasui, Wataru; Mita, Koji; Teishima, Jun; Matsubara, Akio
Abstract : Objectives: To investigate the relationship between chronic kidney disease and primary non‐muscle‐invasive bladder cancer. Methods: Disease outcomes were analyzed in 418 patients treated with transurethral resection for primary non‐muscle‐invasive bladder cancer, and were correlated to traditional risk factors as well as chronic kidney disease stage according to estimated glomerular filtration rate: ≥60 (G1–2), 45–59 (G3a) or <45 (G3b–5). Results: The median follow‐up time was 40.0 months. There were 287 (68.7%), 98 (23.4%), and 33 (7.9%) patients with G1–2, G3a and G3b–5 chronic kidney disease, respectively. T1 tumor was present in 29.6% of G1–2, 43.9% of G3a and 51.4% of G3b–5 chronic kidney disease ( P  = 0.004). The proportion of histological grade 3 non‐muscle‐invasive bladder cancer was higher in G3a and G3b–5 than G1–2 ( P  < 0.001). Higher chronic kidney disease stage was associated with worse recurrence‐free ( P  < 0.001) and progression‐free survival ( P  = 0.017). In multivariable analysis, G3b–5 was found to be an independent predictor for recurrence (hazard ratio 1.87; P  = 0.004) and progression (hazard ratio 2.96; P  = 0.019). Chronic kidney disease stage was also strongly associated with the European Association of Urology bladder cancer risk groups ( P  < 0.001), and with shorter time to recurrence and progression in each group. Conclusions: Chronic kidney disease predicts the clinical outcome of primary non‐muscle‐invasive bladder cancer. Adding chronic kidney disease to the conventional risk factors might increase the accuracy of risk stratification.